Imaging in Bariatric Surgery (Springer International Publishing, 2018)
This book offers detailed guidance on the use of imaging in the context of bariatric surgery. After a summary of the types of surgical intervention, the role of imaging prior to and after surgery is explained, covering both the normal patient and the patient with complications. The most common pathologic features that may be encountered in daily practice are identified and illustrated, and in addition the treatment of complications by means of interventional radiology and endoscopy is described. The authors are acknowledged international experts in the field, and the text is supported by surgical graphs and flow charts as well as numerous images. Overweight and obesity are very common problems estimated to affect nearly 30% of the world's population; nowadays, bariatric surgery is a safe and effective treatment option for people with severe obesity. The increasing incidence of bariatric surgery procedures makes it imperative that practitioners have a sound knowledge of the imaging appearances of postoperative anatomy and potential complications, and the book has been specifically designed to address the lack of knowledge in this area.